SEKOLAH YANG RESPONSIF GENDER (STUDI PADA SMKN 5 KENDARI) - Ety Nur Inah; Rudiyanto R; Aeni Kharunnisa (Institut Agama Islam Negeri Kendari, 2019)
This study aimed to reveal how the description of gender responsive school management as well as gender responsive facilities and infrastructure in teacher secondary schools, especially at state vocational high school 5 Kendari. This research is a qualitative research with data collection through interviews. The results of the study illustrated that school management that is gender responsive in terms of the placement of the principal's position broadly opens opportunities for teachers to occupy strategic positions regardless of male or female gender but based on competence and responsibility and has implemented gender equality and justice in all things, as well as in service in schools provide opportunities for male and female teachers to attend training outside the school and apply disaggregated data in order to facilitate obtaining information about the school in this case school administration. In addition to school management that has been gender responsive and the results of the research show that the tools that support learning are facilities and infrastructure that are also gender responsive, including the use of classrooms, toilet rooms, prayer rooms (mosques) and laboratory room seats.